1998
DOI: 10.1182/blood.v92.6.1941
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Adenovector-Transduced Autologous Tumor Cells Induce Antitumor Immune Responses in Patients With Neuroblastoma

Abstract: In many different murine models, the immunogenicity of tumor cells can be increased by transduction with a range of immunostimulatory genes, inducing an immune response that causes regression of pre-existing unmodified tumor cells. To investigate the relevance of these animal models to pediatric malignancy, we used autologous unirradiated tumor cells transduced with an adenovirus-IL-2 to immunize 10 children with advanced neuroblastoma. In a dose-escalation study, we found that this tumor immunogen induced a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 96 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Recent experience with immunotherapy for neuroblastoma has shown that this tumor is indeed amenable to immune‐mediated cytotoxicity. Treatment of neuroblastoma with an IL‐2 gene‐transduced autologous tumor cell vaccine has produced clinically effective antitumor immune responses in children with advanced neuroblastoma 1. However, the clinical use of this highly individualized strategy is limited by the requirements for in vitro culture and transduction of each patient's tumor cells.…”
mentioning
confidence: 99%
“…Recent experience with immunotherapy for neuroblastoma has shown that this tumor is indeed amenable to immune‐mediated cytotoxicity. Treatment of neuroblastoma with an IL‐2 gene‐transduced autologous tumor cell vaccine has produced clinically effective antitumor immune responses in children with advanced neuroblastoma 1. However, the clinical use of this highly individualized strategy is limited by the requirements for in vitro culture and transduction of each patient's tumor cells.…”
mentioning
confidence: 99%
“…Such regimens include oral etoposide19, 20 and topotecan with/without cyclophosphamide,18, 25, 26 and are compatible with many normal childhood activities. Second, emerging biologic therapeutic agents such as cis ‐retinoic acid,4 fenretinide,42 anti‐G D2 MoAbs,33, 34, 43 and antiidiotype vaccines44‐46 may prove effective in achieving or consolidating remissions. In addition, these agents are generally accepted as being nontoxic to children.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether antibodies with distinct specificity or at higher frequency can be found after tumor vaccination, we also screened a library based on neuroblastoma patients who had received an autologous IL2gene-modified tumor cell vaccine, resulting in the gen- eration of a systemic antitumor response, including cytotoxic, T helper, and specific antibody responses [5].…”
Section: Discussionmentioning
confidence: 99%
“…For the immunized patients library, peripheral blood samples were obtained at monthly intervals from three pediatric patients with relapsed neuroblastoma, 3-10 months after the first injection of an IL-2 gene-modified autologous tumor cell vaccine (Table Ia). All three patients had shown a significant tumor response to the vaccine [5]. For the naive neuroblastoma patients library, peripheral blood and bone marrow lymphocytes were collected from 13 neuroblastoma patients at diagnosis prior to treatment ( Table Ib).…”
Section: Materials and Methods Patient Lymphocytesmentioning
confidence: 99%